Synovial Macrophages in Osteoarthritis: The Key to Understanding Pathogenesis? - Thomson, Amanda; Hilkens, Catharien M. U. (Frontiers in Immunology, 2021)
Effective treatment of osteoarthritis (OA) remains a huge clinical challenge despite major research efforts. Different tissues and cell-types within the joint contribute to disease pathogenesis, and there is great heterogeneity between patients in terms of clinical features, genetic characteristics and responses to treatment. Inflammation and the most abundant immune cell type within the joint, macrophages, have now been recognised as possible players in disease development and progression. Here we discuss recent findings on the involvement of synovial inflammation and particularly the role of synovial macrophages in OA pathogenesis. Understanding macrophage involvement may hold the key for improved OA treatments.